Prevalent Morphometrically Assessed Vertebral Fractures in Individuals With Type 2 Diabetes, Prediabetes and Normal Glucose Metabolism: The Maastricht Study - van Hulten, Veerle; Sarodnik, Cindy; Driessen, Johanna H. M.; Schaper, Nicolaas C.; Geusens, Piet P. M. M.; Webers, Carol A. B.; Dinant, Geert-Jan; Ottenheijm, Ramon P. G.; Rasmussen, Nicklas H.; Viggers, Rikke; Stehouwer, Coen D. A.; van der Kallen, Carla J. H.; et al. (Frontiers in Endocrinology, 2022)
Background: Type 2 diabetes (T2D) is frequently reported to be associated with an increased fracture risk. Epidemiological data on prevalent morphometric vertebral fractures (VFs) in T2D are sparse and even less is known in the prediabetic state. Purpose: To determine the association between prevalence and severity of morphometric VFs and glucose metabolism state: normal glucose metabolism (NGM), impaired glucose metabolism (prediabetes) or T2D. Methods: This study included cross-sectional data from 3625 participants of the Maastricht Study who had a vertebral fracture assessment on lateral Dual Energy X-Ray Absorptiometry images. VFs were classified based on morphometric assessment into mild, moderate and severe VFs (respectively 20–24%, 25–39% or ≥40% reduction in expected vertebral body height). Logistic regression models were used to investigate the association between glucose metabolism status and the prevalence and severity of VFs. Analyses were adjusted for comorbidities, and life-style factors. Results: T2D individuals were older (62.8 ± 7.5 years old) and less often female (30.5%) compared to the NGM group (57.7 ± 8.5 years old, and 58.8% female, respectively). At least one mild, moderate or severe prevalent VF was found in 8.6% of the men and 2.2% of the women in the T2D group, in 9.4% and 8.4% in the prediabetes group and in 9.1% and 4.8% in the NGM group, respectively. After adjustment T2D in women was associated with a lower probability of having a prevalent VF compared to NGM (adjusted OR 0.25 (95% CI 0.09-0.65)), while this was not the case for prediabetes. Furthermore, women with T2D had a significantly lower probability of a prevalent moderate or severe VF (adjusted OR 0.32 (95% CI 0.11-0.96)). In men there was no significant association between T2D or prediabetes and prevalent VFs. Conclusion: Women with T2D had had a lower probability of prevalent VFs compared to women with a normal glucose metabolism, while this was not the case for men with T2D and participants with prediabetes.